HISTOPATHOLOGICAL AND IMMUNO-HISTOCHEMICAL EVALUATION OF MALE AND FEMALE REPRODUCTIVE SYSTEMS OF PORCINE CIRCOVIRUS-2 INFECTED PIGS - Jessil Joseph; Dhanush Krishna Balakrishnan-Nair; R. Anoopraj; P. M. Priya; Chintu Ravishankar; P.S. Arathy; K.S. Prasanna; Safeer M. Saifudeen (Exploratory Animal and Medical Research, 2023)
Porcine Circovirus-2 (PCV-2) is an emerging swine infection responsible for significant financial losses in the global swine industry. It has a significant negative impact on reproductive performance causing abortion, stillbirth, and other anomalies. As there is limited knowledge related to the histopathology of male and female reproductive systems in PCV-2 infected pigs, the current study was designed. Swine carcasses presented for post-mortem examination with a history of respiratory distress, anorexia, diarrhoea, wasting, and paleness of the skin collected from mid of 2021 to mid of 2022 from different parts of Kerala, India, were utilised in this study. The samples were initially screened with polymerase chain reaction (PCR) and were subjected to gross and histopathological studies. Out of 65 collected samples, 10 were positive for PCV-2 by PCR. The positive sample carcasses were emaciated, had poor body condition with visible bony prominences, decreased back fat thickness, rough, long hair coat, and sunken eyes. Mild oedema and congestion were seen in the testes, epididymis, and vas deferens of the male reproductive system and on accessory reproductive glands such as the bulbourethral gland, prostate gland, and seminal vesicle. In the female reproductive system, the ovary, oviduct, and uterus had mild congestion and oedema in most cases. Histopathology of the male reproductive system revealed mild degenerative changes, haemorrhage, and congestion in all cases. The vasa deferentia showed a loss of cilia in the pseudostratified columnar epithelium. The female reproductive organs had congestion, degenerative changes, and infiltration of mononuclear cells. For further confirmation, localisation of PCV-2 antigen was done in reproductive organs with immunohistochemistry (IHC). History, gross, histopathological findings, and PCR in combination with IHC highlight the pathologic effects of PCV-2 on reproductive organs in infected pigs.